P776 Factors associated with quality of care perceived by patients in IBD units from Spain. Analysis from IQCARO project. (25th January 2019) - Casellas, F; Carpio, D; Minguez, M; Vera, I; Juliá, B; Marin, L; Saldaña, R; Cea, L; Calvet, X
Abstract: Background: Measuring patient's perceived quality of care (QoC) in inflammatory bowel disease (IBD) units is becoming increasingly important. The aim of this analysis was to assess the factors associated with QoC of IBD units from Spain, by measuring the fullfillment of a validated score of indicators by patients followed up by IBD specialists or general gastroenterologists (GG). Methods: A survey was developed including patient's sociodemographic and clinical characteristics, as well as the final validated top 10 indicators of QoC. The survey was distributed online through the Spanish Association of Patients with Crohn's disease and ulcerative colitis (ACCU) webpage. In the multi-variate analysis the QoC index score was dichotomised (high quality/low quality) with a cut-off point of 9.5 to be used as a dependent variable in a binary logistic regression model to determine the factors that can influence the evaluation of QoC as high. Results: Online-completed surveys from 640 patients were valid for analysis, with 451 patients (70%) being attended by IBD specialist and 138(30%) by GG. The population included patients from the 17 Spanish autonomous communities, and 183 sites. Mean age was 42.3 years, and mean disease duration 13 years. Sixty-six per cent were women and 60.7% were diagnosed with Crohn's disease. The QoC index mean was 7.8/10 being higher (meaning better QoC) in patients attended by IBD specialists vs. GG: 8.2 vs. 6.7, respectively, p < 0.001. We found no differences regarding disease activity, number of flares, hospitalisations, emergency room visits in the last year or patients′ perception of disease control in the last 2 weeks, in patients attended by IBD specialist vs. GG, p = NS for all. When we analysed the QoC index score as a dichotomised variable, in the univariate analysis we found that older patients, longer disease duration, routine follow-up by IBD specialist, and better perception of controlled disease were all associated with high quality index score. Active disease, unscheduled visits in the last year, higher number of flares, and unemployed patients perceived low quality index score. The multi-variate analysis showed that employed patients, controlled disease, low number of unscheduled visits and being treated by an IBD specialist were all associated with a higher QoC index score. Binary logistic regression analysis. Conclusions: The evaluation of QoC by IBD patients from Spain is good but is higher when they are followed-up by IBD specialists. Personal and disease-related aspects may influence in the perceived QoC.